Answer:
D = -6, E = -8 , F = 0
Explanation:
standard form =
![x^(2) + y^(2) + Dx + Ey + F = 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/sse8n9erkm8ymt71jklhetuwhpv6e0eiw5.png)
now, when circle passes through (3,-1);
⇒
![3^(2) + (-1)^(2) + D(3) + E(-1) + F = 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/auhh9oma4nyiisxrqvys8bpjfv6m5kzyv4.png)
⇒
...............( equation 1)
when circle passes through (-2,4);
⇒
![(-2)^(2) + 4^(2) + D(-2) + E(4)+ F = 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/hdh3qjsa1o1e34tdpdb2rfya8oo297h95y.png)
⇒
...............( equation 2)
when circle passes through (6,8);
⇒
![6^(2) + 8^(2) + D(6) + E(8) + F = 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8fnf2et6l88biqwepenf0lnr5lp1dnxwaz.png)
⇒
................( equation 3)
by solving these 3 equations , we get;
D = -6, E = -8, F = 0
hence,
standard form =
![x^(2) + y^(2) + Dx + Ey + F = 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/sse8n9erkm8ymt71jklhetuwhpv6e0eiw5.png)
=
![x^(2) + y^(2) - 6x - 8y = 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/x4ub3jb2qtugmrjorgijszia1zqliosejw.png)